Uso de datos en la promoción de la mejora (Use of data in the promotion of improvement) - Datnow, Amanda; Schildkamp, Kim (Revista Eletrônica de Educação, 2019)
Encouraging the use of data among teachers requires explicit directive action. Achieving this can have a significant impact on school improvement. Empirical studies, which both authors have directed in their respective countries, allow them to affirm from the evidence that, beyond the marked differences between both educational systems, there is a set of directive practices that favor a use of data that contributes to improvement. Among them, the managers give meaning and projection to the use of data by teachers, creating the organizational conditions so that the use of generated information can be a systematic practice within each institution center. For this, the authors also highlight the importance of the directive function in terms of intellectual stimulation around the use of data with teachers in the school. Resumo Incentivar o uso de dados entre professores requer uma ação diretiva explícita. Conseguir isso pode ter um impacto significativo na melhora da escola. Os estudos empíricos que ambos os autores dirigiram em seus respectivos países permitem afirmar que, além das diferenças marcantes entre os dois sistemas educacionais, há um conjunto de práticas diretivas que favorecem o uso de dados que contribuem para a melhora. Entre eles, os gestores dão sentido e projeção ao uso de dados pelos professores, criando as condições organizacionais para que o uso da informação gerada seja uma prática sistemática dentro de cada instituição. Para isso, os autores também destacam a importância da função do gestor em relação a estimular o uso de dados entre os professores na escola. Resumen Incentivar el uso de datos entre los docentes requiere de una acción directiva explícita. Lograrlo puede impactar significativamente en la mejora escolar. Estudios empíricos que ambas autoras han dirigido en sus respectivos países, les permiten afirmar a partir de la evidencia que, más allá de las marcadas diferencias entre ambos sistemas educativos, existe un conjunto de prácticas directivas que favorecen un uso de datos que contribuya al mejoramiento. Entre ellas, el que los directivos den sentido y proyección al uso de datos por parte de los docentes, creando las condiciones organizacionales para que la utilización de información generada, sea una práctica sistemática al interior de cada centro. Para ello, las autoras también relevan la importancia de la función directiva en cuanto a la estimulación intelectual en torno al uso de datos con los docentes en la escuela. Keywords: Use of data, Directors, Teachers, School. Palavras-chave: Uso de dados, Diretores, Professores, Escola. Palabras claves: Uso de datos, Directores, Profesores, Escuela. References AKKERMAN, S.; BRUINING, T. Multilevel boundary crossing in a professional development school partnership. Journal of the Learning Sciences, 25(2), 2016, pp. 240-284. ARGOTE, L. Organizational Learning: creating, retaining and transferring knowledge. Boston: Kluwer, 1999. AVALOS, B. Teacher professional development in teaching and teacher education over ten years. Teaching and teacher education, 27(1), 2011, pp.10-20. BALL, D. L.; COHEN, D. K. Developing practice, developing practitioners: towards a practice-based theory of professional development. In: L. DARLING-HAMMOND & G. SKYES (Eds.), Teaching as the learning profession: handbook of policy and practice. San Francisco, CA: Jossey-Bass, 1999, pp. 3–32 BINKHORST, F.; HANDELZALTS, A.; POORTMAN, C. L.; VAN JOOLINGEN, W. R. Understanding teacher design teams–a mixed methods approach to developing a descriptive framework. Teaching and teacher education, 51, 2015, pp. 213-224. BORKO, H. Professional development and teacher learning: mapping the terrain. Educational Researcher, 33(8), 2004, pp.3–15. CARLSON, D.; BORMAN, G.; ROBINSON, M. A multistate district-level cluster randomized trial of the impact of data-driven reform on reading and mathematics achievement. Educational Evaluation and Policy Analysis, 33(3), 2011, pp. 378–398. doi: 10.3102/0162373711412765. DARLING-HAMMOND, L. The flat world and education: how America’s commitment to equity will determine our future. New York, NY: Teachers College Press, 2010. DATNOW, A.; CHOI, B.; PARK, V.; ST. JOHN. E. Teacher talk about student ability and achievement in the era of data-driven decision making. Teachers College Record, (In press, 2017). DATNOW, A.; PARK, V.; KENNEDY-LEWIS, B. Affordances and constraints in the context of teacher collaboration for the purpose of data use. Journal of Educational Administration, 51(3), 2013, pp.341–362. DATNOW, A.; PARK, V. Data-driven leadership. San Francisco: Jossey Bass, 2014. DATNOW, A.; PARK, V. Data use for equity. Educational Leadership, 72(5), 2015, pp.49-54. DATNOW, A.; PARK, V.; KENNEDY, B. Acting on data: how urban high schools use data to inform instruction. Los Angeles, CA: Center on Educational Governance, USC Rossier School of Education, 2008. DAVIS, B.; SUMARA, D.; D’AMOUR, L. Understanding school districts as learning systems: some lessons from three cases of complex transformation. Journal of Educational Change, 13(3), 2012, pp.373–399. EARL, L. M.; KATZ, S. Leading schools in a data-rich world. Harnessing data for school improvement. Thousand Oaks, CA: Corwin Press, 2006. FARLEY-RIPPLE, E. N.; BUTTRAM, J. L. Developing collaborative data use through professional learning communities: early lessons from Delaware. Studies in Educational Evaluation, 42, 2014, pp.41–53. FELDMAN, M. S.; PENTLAND, G. T. Reconceptualizing organizational routines as a source of flexibility and change. Administrative Science Quarterly, 48, 2003, pp.94-118. FIRESTONE, W. A.; GONZÁLEZ, R. A. Culture and processes affecting data use in school districts. In: P. A. MOSS (Ed.), Evidence and decision making. Yearbook of the National Society for the Study of Education. Malden, MA: Blackwell, 2007, pp. 132-154. GEIJSEL, F. P.; SLEEGERS, P. J. C.; STOEL, R. D.; KRÜGER, M. L. The effect of teacher psychological, school organizational and leadership factors on teachers’ professional learning in Dutch schools. The Elementary School Journal, 109(4), 2009, pp.406–427. GEIJSEL, F.; SLEEGERS, P.; LEITHWOOD, K.; JANTZI, D. Transformational leadership effects on teachers’ commitment and effort toward school reform. Journal of Educational Administration, 41(3), 2003, pp.228–256. HORN, I.; KANE, B.; WILSON, B. Making sense of student performance data: data use logics and mathematics teachers’ learning opportunities. American Educational Research Journal, 52(2), 2015, pp.208-242. IKEMOTO, G. S.; MARSH, J. A. Chapter 5 Cutting through the “Data?Driven” Mantra: different conceptions of datadriven decision making. Yearbook of the National Society for the Study of Education, 106(1), 2007, pp.105-131. HUBERS, M.D.; MOOLENAAR, N.M.; SCHILDKAMP, K.; DALY, A.J.; HANDELZALTS, A.; PIETERS, J.M. Share and succeed: the development of knowledge sharing and brokerage in data teams’ network structures. Research Papers in Education, 2017. DOI: 10.1080/02671522.2017.1286682. HUNTER, S. T.; BEDELL-AVERS, K. E.; MUMFORD, M. D. The typical leadership study: assumptions, implications, and potential remedies. The Leadership Quarterly, 18, 2007, pp. 435–446. doi:10.1016/j.leaqua.2007.07.001. KERR, K. A.; MARSH, J. A.; IKEMOTO, G. S.; DARILEK, H.; BARNEY, H. Strategies to promote data use for instructional improvement: actions, outcomes, and lessons from three urban districts. American Journal of Education, 112, 2006, pp. 496–520. LAI, M. K.; WILSON, A.; MCNAUGHTON, S.; HSIAO. S. Improving achievement in secondary schools: impact of a literacy project on reading comprehension and secondary schools qualifications. Reading Research Quarterly, 49(3), 2014, pp.305–334. doi: 10.1002/rrq.73. LEITHWOOD, K.; JANTZI, D. Transformational school leadership for large-scale reform: effects on students, teachers, and their classroom practices. School Effectiveness and School Improvement, 17(2), 2006, pp.202–227. LEVIN, J. A.; DATNOW, A. The principal role in data-driven decision making: using case-study data to develop multi-mediator models of educational reform. School Effectiveness and School Improvement, 23(2), 2012, pp.179–201. LOMOS, C.; HOFMAN, R. H.; BOSKER, R. J. Professional communities and student achievement – a meta-analysis. School Effectiveness and School Improvement, 22, 2011, pp.121–148. MANDINACH, E. B.; GUMMER, E. S. A systemic view of implementing data literacy in educator preparation. Educational Researcher, 42(1), 2013, pp.30–37. MARSH, J. A. Interventions promoting educators’ use of data: research insights and gaps. Teachers College Record, 114(11), 2012, pp.1–48. MOOLENAAR, N. M.; SLEEGERS, P. J. C.; DALY, A. J. Teaming up: linking collaboration networks, collective efficacy, and student achievement. Teaching and Teacher Education, 28, 2012, pp. 251–262. doi:10.1016/j.tate.2011.10.001. PARK, V.; DALY, A.J.; GUERRA, A.W. Strategic framing: how leaders craft the meaning of data use for equity and learning. Educational Policy, 27(4), 2013, pp. 645-675. PARK, V.; DATNOW, A. Co-constructing distributed leadership: district and school connections in data-driven decision-making. School Leadership and Management, 29(5), 2009, pp. 477–494. PARK, V.; DATNOW, A. Ability grouping and differentiated instruction in an era of data-driven decision making. American Journal of Education, 123(2), 2017, pp.281-306. POORTMAN, C.L.; SCHILDKAMP, K. Solving student achievement focused problems with a data use intervention for teachers. Teaching and Teacher Education, 60, 2016, pp.425-433. ROEHRIG, A. D.; DUGGAR, S. W.; MOATS, L.; GLOVER, M.; MINCEY, B. When teachers work to use progress monitoring data to inform literacy instruction: identifying potential supports and challenges. Remedial and Special Education, 29(6), 2008, pp.364–382. doi: 10.1177 /0741932507314021 SCHILDKAMP, K.; HANDELZALTS, A.; POORTMAN, C.L.; LEUSINK, H.; MEERDINK, M.; SMIT, M.; EBBELER, J.; HUBERS, M.D. The data teamtm procedure: a systematic approach to school improvement. Dordrecht: Springer, 2017. SCHILDKAMP, K.; POORTMAN, C.L. Factors influencing the functioning of data teams. Teachers College Record, 117(4), 2015, pp.1-42. SCHILDKAMP, K.; EHREN, M. From “Intuition”-to “Data”-based decision making in Dutch Secondary Schools? In: K. SCHILDKAMP, K.K. LAI AND L. EARL (Eds.). Data-based decision making in education: challenges and opportunities. Dordrecht: Springer, 2013, pp. 49-67. SCHILDKAMP, K.; POORTMAN, C.L.; EBBELER, J.; PIETERS, J.M. (artículo presentado). The role of school leaders in data teams. SCHILDKAMP, K.; KUIPER, W. Data-informed curriculum reform: which data, what purposes, and promoting and hindering factors. Teaching and Teacher Education, 26, 2010, pp.482-496. SPILLANE, J. P. Data in practice: conceptualizing the data-based decision-making phenomena. Teachers College Record, 118(2), 2012, pp.113-141. SPILLANE, J. P.; CAMBURN, E. M.; STITZIEL PAREJA, A. Taking a distributed perspective to the school principal’s workday. Leadership and policy in schools, 6(1), 2007, pp.103-125. STOLL, L.; BOLAM, R.; MCMAHON, A.; WALLACE, M.; THOMAS, S. Professional learning communities: a review of the literature. Journal of Educational Change, 7, 2006, pp.221–258. SUTHERLAND, S. Creating a culture of data use for continuous improvement: a case study of an Edison project. American Journal of Evaluation, 25(3), 2004, pp.277–293. doi: 10.1177 /109821400402500302. THOONEN, E. E. J.; SLEEGERS, P. J. C.; OORT, F. J.; PEETSMA, T. T. D.; GEIJSEL, F. P. How to improve teaching practices: the role of teacher motivation, organizational factors and leadership practices. Educational Administration Quarterly, 47(3), 2011, pp.496–536. VAN GEEL, M.; KEUNING, T.; VISSCHER, A. J.; FOX, J. P. Assessing the effects of a school-wide data-based decision-making intervention on student achievement growth in primary schools. American Educational Research Journal, 53(2), 2016, pp.360-394. VANHOOF, J.; VERHAEGHE, G.; VAN PETEGEM, P.; VALCKE, M. Flemish primary teachers’ use of school performance feedback and the relationship with school characteristics. Educational Research, 54(4), 2012, pp. 431–449. VESCIO, V.; ROSS, D.; ADAMS, A. A review of research on the impact of professional learning communities on teaching practice and student learning. Teaching and Teacher Education, 24, 2008, pp.80–91. WAYMAN, J. C.; CHO, V.; SPIKES, D. D. District-wide effects on data use in the classroom. Education Policy Analysis Archives, 20(25), 2012. Recuperado el 5 de mayo de 2013 en http://epaa.asu.edu/ojs/article/view/979. WAYMAN, J. C.; STRINGFIELD, S. Technology-supported involvement of entire faculties in examination of student data for instructional improvement. American Journal of Education, 112(4), 2006, pp.549–571. doi: 10.1086/505059. WOHLSTETTER, P.; DATNOW, A.; PARK, V. Creating a system for data-driven decision-making: applying the principal-agent framework. School Effectiveness and School Improvement, 19(3), 2008, pp. 239–259. doi: 10.1080/09243450802246376. YOUNG, V. M. Teachers’ use of data: loose coupling, agenda setting, and team norms. American Journal of Education, 112, 2006, 521–548.